2013
DOI: 10.1088/0004-637x/769/1/45
|View full text |Cite
|
Sign up to set email alerts
|

On Sun-to-Earth Propagation of Coronal Mass Ejections

Abstract: We investigate how coronal mass ejections (CMEs) propagate through, and interact with, the inner heliosphere between the Sun and Earth, a key question in CME research and space weather forecasting. CME Sun-to-Earth kinematics are constrained by combining wide-angle heliospheric imaging observations, interplanetary radio type II bursts and in situ measurements from multiple vantage points. We select three events for this study, the 2012 January 19, 23, and March 7 CMEs. Different from previous event studies, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
222
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(262 citation statements)
references
References 69 publications
35
222
3
2
Order By: Relevance
“…In that case, the ICME arrives at 1 au with almost the same speed as the background solar wind. This behavior is consistent with the two-phased deceleration characteristics of ICMEs reported by Liu et al (2013). When the CME is as heavy as =Ḿ 3 10 0 16 g (thick lines), the ICME arrives at 1 au, with a larger speed compared to the =Ḿ 3 10 0 15 g cases.…”
Section: The Icme Propagation Characteristics In the Sap Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…In that case, the ICME arrives at 1 au with almost the same speed as the background solar wind. This behavior is consistent with the two-phased deceleration characteristics of ICMEs reported by Liu et al (2013). When the CME is as heavy as =Ḿ 3 10 0 16 g (thick lines), the ICME arrives at 1 au, with a larger speed compared to the =Ḿ 3 10 0 15 g cases.…”
Section: The Icme Propagation Characteristics In the Sap Modelsupporting
confidence: 88%
“…They have studied with the use of global MHD simulations in 3D (Manchester et al 2004;Lugaz & Roussev 2011;Shiota & Kataoka 2016). Liu et al (2013) reported the first detailed examination of the Sun-to-Earth propagation characteristics of three fast CMEs and an associated shock front using the combination of wideangle heliospheric imaging observations by STEREO, interplanetary Type II radio bursts, and in situ observations of solar wind parameters at multiple points. They reported that CME Sun-to-Earth propagation can be approximately formulated into three phases: (1) an impulsive acceleration near the Sun (up tõ 0.1 au), (2) rapid deceleration up to the distance of 0.2 0.4 au -, and (3) nearly constant speed propagation or gradual deceleration afterward.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of earlier studies regarding the relative performance of the reconstruction methods (Lugaz, 2010;Liu et al, 2013;Mishra, Srivastava, and Davies, 2014), we applied the stereoscopic self-similar expansion (SSSE) method to the J-maps of the interacting CMEs in the present study. The SSSE method is expected to yield better results as the CMEs were observed in HI field of view of both STEREO-A and B.…”
Section: D Reconstruction Of Interacting Cmes In Hi Fovmentioning
confidence: 99%
“…After the launch of twin Solar TErrestrial Relations Observatory spacecraft (STEREO: Kaiser et al 2008), the data from the Sun Earth Connection Coronal and Heliospheric Investigation (SECCHI: Howard et al 2008) have enabled us to continuously image CMEs from their lift-off in the corona up to the Earth and beyond Harrison et al, 2012;Liu et al, 2013;Möstl et al, 2015;Vemareddy and Mishra, 2015). These observations have also revealed direct evidence of CME-CME interaction when they are launched in close succession in the same direction Lugaz et al, 2012;Shen et al, 2012;Mishra, Srivastava, and Chakrabarty, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wood, Howard, and Socker, 2010;Liu et al, 2013). These techniques are usually used to determine the motion of transients travelling in the ecliptic plane, although can be applied out of the ecliptic.…”
Section: J-maps and Time-elongation Profile Fittingmentioning
confidence: 99%